Relationship between vertical jump parameters and changes in agility performance following post-activation potentiation in elite fencers - Yildirim, E.; Koç, H. (Turkish Journal of Sport and Exercise, 2025)
This study aimed to examine the relationship between vertical jump-derived neuromuscular parameters and agility performance changes following post-activation potentiation (PAP) protocols in elite fencers. Seventeen elite male fencers (age: 17.29 ± 1.93 years) performed vertical jump assessments - countermovement jump (CMJ), squat jump (SJ), and drop jump (DJ) - using the Optojump Next system. Reactive strength index (RSI), relative power, and other jump metrics were recorded. PAP was elicited via Smith machine split squat protocols (dominant, non-dominant, bilateral legs), while agility was measured using a 4-2-2-4 test at 1, 3, 5, and 7 minutes post-PAP, timed via photocell gates. A repeated-measures ANOVA, Pearson correlations, and multiple linear regressions were conducted to identify predictive relationships. A significant main effect of time was observed on agility performance (F(4,64) = 11.103, p < 0.001, (U+03C9)² = 0.110), while no significant main effect of condition emerged. A small but significant interaction effect (F(12,192) = 1.866, p = 0.041, (U+03C9)² = 0.017) suggested time-dependent differences among conditions. However, post hoc tests and simple effects analyses did not yield significant contrasts. Regression models revealed that DJ flight time and DJ height were the most consistent predictors of agility changes, particularly in the bilateral and control groups. CMJ and SJ variables demonstrated moderate predictive relevance. Although PAP protocols led to temporal improvements in agility, no substantial differences were found between conditions. Vertical jump-derived parameters, especially DJ characteristics, may help identify individuals more responsive to PAP. These findings suggest the need for individualized PAP programming in elite fencers.